Understanding the city as Habitat and Habitus - Xyntarianos Tsiropinas, Paris (2020)
Our understanding and use of the urban environment is constantly changing. Applied sciences, technology, creativity, design, architecture, art and imagination play an important role in the continuous reconstruction of cities, whether they are a modern megacity or a small provincial town. Graffiti and Street Art have taken on prominent positions in dialectics of urban design, which encourages more views in more and more locations. In an attempt to follow the explosive developments and realize its vision, a group of people created a Street Art Festival in Hermoupolis, Syros, the capital of Cyclades archipelago. This paper presents the design of festival with respects to strategy, vision and values that govern it. In addition, its changing relationship with the concepts of growth and sustainability is addressed and analyzed, and its impact on the day-to-day lives of residents and visitors as well as on the development of cultural capital is recorded. In conclusion, Stray Art Festival seems to be able to be temporally sustainable by being able to attract a critical number of returning visitors and locals, who, like the festival organizing team, live and perceive the city as a vibrant and constantly changing region, for which they are invited to contribute their knowledge, their ingenuity and ideas, or simply their constant presence, thus becoming active members of a creative community that aims to take the city back.